2018
DOI: 10.5114/aoms.2017.65650
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of methylprednisolone and tetracosactide (ACTH 1–24 ) on ischemia/reperfusion injury of the rabbit spinal cord

Abstract: IntroductionTetracosactide is an engineered peptide that applies the same biological impacts as the endogenous adrenocorticotropic hormone. Previous studies indicated that tetracosactide has anti-inflammatory, antioxidant and neurotrophic activity. In this study, we hypothesized that tetracosactide may have protective effects in spinal cord ischemia-reperfusion injury.Material and methodsRabbits were randomized into the accompanying four groups of eight animals each: group 1 (control), group 2 (ischemia), grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In addition, we examined MDA and 8-iso-PGF2α, which are indicators of the oxidative status [ 33 ]. Spinal cord ischemia significantly increased the MDA and 8-iso-PGF2α levels in the spinal cord, and these results are consistent with previous studies that showed that spinal cord ischemia increased biomarkers of free radical damage [ 5 , 8 , 34 ]. Treatment with Tat-PGAM1, and not Control-PGAM1, significantly ameliorated the increase in MDA and 8-iso-PGF2α levels in the spinal cord.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we examined MDA and 8-iso-PGF2α, which are indicators of the oxidative status [ 33 ]. Spinal cord ischemia significantly increased the MDA and 8-iso-PGF2α levels in the spinal cord, and these results are consistent with previous studies that showed that spinal cord ischemia increased biomarkers of free radical damage [ 5 , 8 , 34 ]. Treatment with Tat-PGAM1, and not Control-PGAM1, significantly ameliorated the increase in MDA and 8-iso-PGF2α levels in the spinal cord.…”
Section: Discussionsupporting
confidence: 92%
“…Three parameters (congestion, myocyte dissociation, inflammation) of heart tissue were evaluated histopathologically and graded as follows: 0, none; 1, mild; 2, moderate; and 3, severe. The histopathology score of heart tissue of each animal in all groups was the average of these three parameters .…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of M1 to M2 influences the microenvironment of the spinal cord tissue after injury, as the augmentation of M1 phenotype after SCI will negatively affect the injury repair (Fan et al, 2018). Besides, reactive oxygen species (ROS) can lead to cell and tissue dysfunction through the oxidation of DNA and cell membranes, which further causes inflammation (Hervera et al, 2018;Kertmen et al, 2018). SCI comprises of three stages; acute stage, acute secondary stage, and chronic stage (Nukolova et al, 2018).…”
Section: The Role Of Inflammatory Reaction In Sci Progressionmentioning
confidence: 99%